2015
DOI: 10.5935/1518-0557.20150005
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and obstetric outcomes of pregnancies conceived by assisted reproductive technology (ART) compared to non-ART pregnancies

Abstract: Objective: Use of assisted reproductive technology has increased steadily, yet multiple socioeconomic and demographic disparities remain between the general population and those with infertility. Additionally, both mothers and infants experience higher rates of adverse outcomes compared to their non-ART counterparts. Methods: Using International Classification of Diseases, Ninth Revision (ICD-9) coding, we performed a retrospective review of all ART-conceived deliveries in California in 2009. A total of 551 AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Although we did not find a statistically significant difference in pre-term delivery or PreE for the deliveries resulting from pregnancies achieved through fresh IVF cycles, the 14.1% and 5.3% overall rates, respectively were higher than the 5% and 3.9% rates, respectively, of all singleton live births in the literature. [27]…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not find a statistically significant difference in pre-term delivery or PreE for the deliveries resulting from pregnancies achieved through fresh IVF cycles, the 14.1% and 5.3% overall rates, respectively were higher than the 5% and 3.9% rates, respectively, of all singleton live births in the literature. [27]…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Ananth et al [23] reported a higher placenta previa rate in twin pregnancies compared with singleton pregnancies, as well as an increased placenta previa rate with advancing maternal age. Recent studies have identified several risk factors of placenta previa, such as parity, previous cesarean section, advanced maternal age, and multiple pregnancies [232425]. A possible explanation for the increased placenta previa risk is that the placenta size for a twin pregnancy is larger than that of a singleton pregnancy [26].…”
Section: Discussionmentioning
confidence: 99%
“…It showed that clinicians were 3.2 times less likely to recommend amniocentesis for pregnancies conceived from assisted treatment than for a spontaneous pregnancy [19]. Furthermore there are likely demonstrable differences between the socioeconomic status of the two groups: an independent predictor of improved perinatal outcomes [17].…”
Section: Discussionmentioning
confidence: 99%
“…They both found that there was an increased caesarean section rate for assisted conception twins when compared with those spontaneously conceived [15,16]. A recent study further identified an association of ART pregnancies with preeclampsia, placental abruption, placenta praevia and obstructed labour [17]. These associations may provide additional reasoning as to why there is an increased caesarian section incidence in the ART population, beyond the association with higher socioeconomic status [17].…”
Section: Introductionmentioning
confidence: 99%